2018- CSA Monitoring – Cauca Climate Smart-Village (Colombia) - Bonilla Findji, Osana; Eitzinger, Anton; Andrieu, Nadine; Jarvis, Andrew; Martínez Barón, Deissy; Ortega, Luis Alfonso; Mañunga, Jimmy (2019)
This dataset contains the files produced in the implementation of the “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Cauca Climate Smart Village (Colombia) in February 2018. This monitoring framework developed by CCAFS is meant to be deployed annually across the global network of Climate-Smart Villages to gather field-based evidence by tracking the progress on: